Geometric programming technique: Sizing the geometric parameters and performance indices of a single sided linear induction motor - Onoharigho, Okpare, Anthony; Oyubu, Oyubu, Akpovi; Orode, Otuagoma, Smith; Ubiomo, Ubeku, Emmanuel; Ikponmwosa, Oghogho (Edelweiss Applied Science and Technology, 2024)
This paper presents the use of Geometric Programming (GP) technique for the optimal geometric sizing design of a three phase single sided linear induction motor (SLIM). Two objective functions were proposed to enhance the determination of the best sizing parameters, while, nine constraints were imposed on the objective function using the GP tool in the MATLAB/Octave environment. Some quantities were chosen as the independent design variables: stator length〖 L〗_s, stator width W_s, stator yoke depthh_y, stator slot width w_s, and stator tooth width w_t; these variables are on the primary of the SLIM. The variables considered on the secondary of the SLIM are the width of back iron W_b and the depth of the back iron T_b.The results suggested that stator losses were 203.4 W, while weight of stator was 6.44 kg. Furthermore, comparison was made with existing SLIM design, and results suggest that GP is a viable technique. Also comparison with the literature showed that the findings of this work are within specified limits.